Significación geográfica de algunas actividades del Servicio Meteorológico de Alemania Federal (estudio metodológico) - Peña Alvarez, Orlando (Investigaciones Geográficas: Una mirada desde el sur, 1977)
In this work are analysed three bearings of the permanent work of the Federal Germany Meteorological Service, whose results can be very well availed by the geographers for their s tudies on Applied Climatology. The Technoclimatology supplies work implements to the Urban and Traffic Climatology, between another specialties, centering her attention on the temperature and humidity distributive patterns inside of the cities and on the surface winds circulation in urban areas and roads. The Meteorology supports very much her action on the phenological observations which, in Federal Germany, are carried regularty through in approximately 3.000 places, distributed in more or less uniform way through the whole country. Those data and other properly climato - meteorological measures are the base of researches on cultivation submissions and agricultural productivity in general. The Regional and Urban Planning, as far as she is concerned, utilizes information on air hygiene and climatic conditions which are obtained, from conventional instruments and through the remote sensing, specialty, the infrated termography. Thus, it is suggested the needs of an enlargement of the developed records and works by our Meteorological Services and their systematic employment by the geographers, thinking pincipally on the participation of these professionals in the development's programs.